Class Management Profiles of Secondary School Teachers - Muhsin Hazar; Malik Beyleroglu; Sakir Bezci; Hacer Ozge Baydar; Emre Ozan Tingaz (European Scientific Journal, ESJ, 2017)
The purpose of this research is to examine the class management profile of secondary school branch teachers working in certain province of Turkey, using some variables. The research group consists of 152 teachers (69 female and 83 male) in the various field of Mathematics (29), Turkish (46), Religion Culture (23), English (31), and Physical Education and Sports (23). The "Classroom Management Profile Scale (SYPÖ)" developed by Kris (1996) and adapted to Turkish by Ekici (2004) was used as the data collection tool in the research. The research was conducted based on both the general and the relational screening models. The SPSS 20.0 package program was used in the analysis of the data. Both T test and one-way ANOVA were used in independent groups to determine whether the gender and subscale of the scale were significantly different according to gender, age, occupation year and field. The results of the research proved that, when the scores of both scales were calculated, the grade management profiles of the teachers were not statistically different according to the considered variables.